Lies that tell the truth : magic realism seen through contemporary fiction from Britain - Hegerfeldt, Anne C. (Costerus ;, 2005)
Magic realism has long been treated as a phenomenon restricted to postcolonial literature. Drawing on works from Britain, Lies that Tell the Truth compellingly shows how magic realist fiction can be produced also at what is usually considered to be the cultural centre without forfeiting the mode's postcolonial attitude and aims. A close analysis of works by Angela Carter, Salman Rushdie, Jeanette Winterson, Robert Nye and others reveals how the techniques of magic realism generate a complex critique of the West's rational-empirical worldview from within a Western context itself. Understanding magic realism as a fictional analogue of anthropology and sociology, Lies that Tell the Truth reads the mode as a frequently humorous but at the same time critical investigation into people's attempts to make sense of their world. By laying bare the manifold strategies employed to make meaning, magic realist fiction indicates that knowledge and reality cannot be reduced to hard facts, but that people's dreams and fears, ideas, stories and beliefs must equally be taken into account.